A Critical Analytic Discussion of Massive Curriculum Pedagogy Comparable to Holly Books-Towards ICTs Strategies - M. Ziad Hamdan (Indonesian Journal Of Educational Research and Review, 2021)
Massive curriculum pedagogies (MCPs) represent an everlasting methodological problem of schooling throughout the Common. Era. Descriptive causal-comparative/ ex-post facto research techniques and Action Developmental Approach were used to objectively comprehend the problem's realities, trace the cause-effect relations between MCPs' factors, and build effective solutions to the MCPs’ research problem. The semantic logical reasoning of results showed strong linkages among the MCPs, the Holly Books' (H.B.s) teaching and the Factory Educational Model 1800+ in sharing extensive large groups learning and instruction. Even curriculum pedagogies took from H.Bs the compulsory learning besides the massive teaching methodology. What is disturbing here is these negative pedagogies are against the welfare of learners in the Info Global Age and the wide diversity of ICTs’ sources available to schooling. Learners have by nature no identical aptitudes, priority knowledge needs, thinking and achievement speeds, timelines, and live spaces for learning and schooling. Considering the research results and the pragmatic principle of ‘nothing can respond to diversity except diversity’, the Author offered a countering strategy (“Schools without Flunking”) merited with personalized, ICTs’ based, and collaborative peers, enabling 97% of learners to achieve the studied "blend-digit" curricula.